The trees eaudiobook - Richter, Conrad (Awakening Land, 2019)
The Awakening Land trilogy traces the transformation of a middle-American landscape from wilderness to farmland to the site of modern industrial civilization, all in the lifetime of one character. The trilogy earned author Conrad Richter immense acclaim, ranking him with the greatest of American mid-century novelists. It includes The Trees (1940), The Fields (1946), and The Town (1950) and follows the varied fortunes of Sayward Luckett and her family in southeastern Ohio. The Trees is the story of an American family in the wilderness—a family that " followed the woods as some families follow the sea ." The time is the end of the eighteenth century, the wilderness is the land west of the Alleghenies and north of the Ohio River. But principally, The Trees is the story of a girl named Sayward, eldest daughter of Worth and Jary Luckett, raised in the forest far from the rest of humankind, yet growing to realize that the way of the hunter must cede to the way of the tiller of soil.